Urinary tuberculosis: a cohort of 79 adult cases. (9th August 2015) - Altiparmak, Mehmet Riza; Trabulus, Sinan; Balkan, Ilker Inanc; Yalin, Serkan Feyyaz; Denizli, Nazim; Aslan, Gonul; Doruk, Hasan Erdal; Engin, Aynur; Tekin, Recep; Birengel, Serhat; Cetin, Birsen Durmaz; Arslan, Ferhat; et al.
Abstract: We aimed to investigate the demographic, clinical, diagnostic, treatment and outcome features of patients with urinary tuberculosis (UTB). Patients with UTB admitted to seven separate centers across Turkey between 1995 and 2013 were retrospectively evaluated. The diagnosis of UTB was made by the presence of any clinical finding plus positivity of one of the following: (1) acid-fast bacilli (AFB) in urine, (2) isolation of Mycobacterium tuberculosis, (3) polymerase chain reaction (PCR) for M. tuberculosis, (4) histopathological evidence for TB. Seventy-nine patients (49.36% male, mean age 50.1 ± 17.4 years) were included. Mean time between onset of symptoms and clinical diagnosis was 9.7 ± 8.9 months. The most common signs and symptoms were hematuria (79.7%), sterile pyuria (67.1%), dysuria (51.9%), weakness (51.9%), fever (43%) and costovertebral tenderness (38%). Cystoscopy was performed in 59 (74.6%), bladder biopsy in 18 (22.8%), kidney biopsy in 1 (1.26%) and nephrectomy in 12 (15.2%) patients. Histopathological verification of UTB was achieved in 12 (63.1%) patients who undergone biopsy and in 100% of those undergone nephrectomy. Mycobacterium tuberculosis was isolated in the urine of 50 (63.3%) cases. Four-drug standard anti-TB treatment was the preferred regimen for 87.3% of the patients. Mean treatment duration was 10.5 ± 2.7 months. Deterioration of renal function occurred in 15 (18.9%) patients two of whom progressed to end-stage renal disease and received hemodialysis. Only one patient died after 74-day medical treatment period. Cases with UTB may present with non-specific clinical features. All diagnostic studies including radiology, cyctoscopy and histopathology are of great importance to exclude UTB and prevent renal failure.